Herself an Author Gender, Agency, and Writing in Late Imperial China - Fong, Grace S. (University of Hawaii Press, 2008)
"Grace Fong has written a wonderful history of female writers' participation in the elite conventions of Chinese poetics. Fong's recovery of many of these poets, her able exegesis and elegant, analytical grasp of what the poets were doing is a great read, and her bilingual presentation of their poetry gives the book additional power. This is a persuasive and elegant study." -Tani Barlow, author of The Question of Women in Chinese Feminism"In this quietly authoritative book, Grace Fong has brought a group of women poets back to life. Previously ignored by scholars because of their marginal status or the inaccessibility of their works, these remarkable writers now speak to us about the sensualities, pains, satisfactions, and sadness of being a woman in a patriarchal society.